Development of an embryo transfer model to study uterine contributions to pregnancy in vivo in mice. Issue 1 (14th February 2022) - Griffiths, Meaghan J; Alesi, Lauren R; Winship, Amy L; Hutt, Karla J
Abstract : Graphical abstract: A mouse model to study uterine specific contributions to pregnancy. Maternal environmental exposures can exert impacts on the ability of the uterus to sustain healthy pregnancy. To establish an in vivo model to study this, we designed an ovariectomized mouse embryo transfer model. The rationale being future studies could expose recipient female mice to variables such as altered diet, drug, temperature, air, or activity exposure among others to define their impacts on the uterine contribution to pregnancy. Ovariectomy ensures the extent of the variable is limited to exploring outcomes on uterine but not ovarian function. Embryo transfer from healthy, unexposed donor mice guarantees that any impacts of the variable are attributed to the maternal uterine but not the embryonic state. Pregnancy outcomes including pregnancy success (number of implantation sites) and viability (number of viable vs resorbing implantation sites) can be investigated. Numerous functional outcomes can be assessed, including developmental competence encompassing decidual, placental, fetal, and vascular morphology and/or function (e.g. measured using Doppler ultrasound, comparisons of fetal growth, or molecular or histological characterization of the decidua, placenta, and fetal tissues). Lay summary: Many pregnancy complications occur because of problems in the womb (uterus), specifically the womb lining. There is a close relationship between the hormone function of the ovaries and the uterus and distinguishing between the way they both impact pregnancy success is difficult in existing studies using animals. Here, we developed a new animal model to utilize in addressing these gaps in our understanding of pregnancy.